1995
DOI: 10.1183/09031936.95.08081318
|View full text |Cite
|
Sign up to set email alerts
|

Preventive therapy for asthma in children; a 9-year experience in eastern Finland

Abstract: P Pr re ev ve en nt ti iv ve e t th he er ra ap py y f fo or r a as st th hm ma a i in n c ch hi il ld dr re en n; ; a a 9 9--y ye ea ar r e ex xp pe er ri ie en nc ce e i in n E Ea as st te er rn n F Fi in nl la an nd d The data on maintenance drugs in children with asthma from five years (1985, 1987, 1989, 1991 and 1993) were retrospectively retrieved from the computerized registers. The reliability of the data for the diagnosis and basic treatment of asthma was checked by one of the authors, who compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0
1

Year Published

1996
1996
2007
2007

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 10 publications
0
10
0
1
Order By: Relevance
“…In our area, all children with chronic or moderate-to-severe asthma are on continuous anti-inflammatory therapy. 30 Serum ECP and EPX concentrations are known to decrease during such therapy, 5,20,31 even if some symptoms persist. 23 Therefore, ECP and EPX values in asthmatic children who were on maintenance medication were as low as in the healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…In our area, all children with chronic or moderate-to-severe asthma are on continuous anti-inflammatory therapy. 30 Serum ECP and EPX concentrations are known to decrease during such therapy, 5,20,31 even if some symptoms persist. 23 Therefore, ECP and EPX values in asthmatic children who were on maintenance medication were as low as in the healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…The highest rates of prophylactic pharmacological treatment have been observed in Finland (80%), in the United Kingdom (52.5%), and in the United States (47.5%). (23)(24)(25) In 1988, one group of authors studied 266 children with asthma hospitalized in Australia and found a much higher percentage of individuals Therefore, we conclude that the rate at which such patients seek outpatient follow-up treatment for asthma is far from acceptable, which may be a reflection of the situation in which we find the Brazilian Unified Health Care System. The present study reveals that, among patients hospitalized for acute asthma, full access to treatment and to preventive medication is the exception.…”
Section: Discussionmentioning
confidence: 61%
“…Unfortunately, reliable information for comparison of SII data was not available on the consumption of antiinflammatory drugs in the area until 1995. However, the hospital-based data, gathered mainly from outpatients, suggested that steroids were clearly used less before the year 1995 [20,27].…”
Section: Discussionmentioning
confidence: 99%